The importance of timing for the spontaneous breathing trial - Perren, Andreas; Brochard, Laurent (Annals of Translational Medicine, 2019)
Weaning intubated patients from mechanical ventilation may be defined as the transition from total ventilatory support to spontaneous breathing, sometimes performed abruptly, sometimes gradually (1). Worldwide, millions of patients are intubated each year for various purposes.